Textile effluent treatment using coagulation-flocculation and a hydrodynamic cavitation reactor associated with ozonation - Marques, Diego Gouveia [UNESP]; de Melo Franco Domingos, Janaina; Nolasco, Marcelo Antunes; Campos, Valquíria [UNESP] (Elsevier, 2025)
Textile effluent is a highly toxic wastewater that resists conventional treatments, requiring advanced technologies for the effective removal of pollutants. A promising solution involves combining processes like coagulation-flocculation and hydrodynamic cavitation with ozone. Coagulation-flocculation, a low-cost method, enhances the effectiveness of subsequent treatments. Hydrodynamic cavitation paired with ozone is described as a synergetic oxidation process that facilitates pollutant removal and mitigates ozone-related limitations. In this study, the combination of coagulation-flocculation and hydrodynamic cavitation with ozone was evaluated. Alone, two hours of cavitation and ozone removed 45 % of apparent color and 56 % of COD, which was insufficient. Coagulation-flocculation with 700 mg L−1 of PACl yielded high pollutant removal but generated significant sludge. Using 550 mg L−1 of PGα21Ca followed by hydrodynamic cavitation and ozone achieved 94 % color, 97 % turbidity, and 84 % COD removal, meeting Brazilian disposal standards, with 86 % less sludge than PACl, highlighting its technical efficacy and potential environmental advantages.
Keywords: Advanced oxidation process; Apparent color; COD; Sludge formation